An introduction to English sociolinguistics - Trousdale, Graeme, 1971- (Edinburgh textbooks on the English language., 2010)
This textbook, aimed primarily at beginning undergraduates studying for degrees in English, provides an introduction to a range of sociolinguistic theories and the insights they provide for a greater understanding of varieties of English, past and present. Drawing on both qualitative and quantitative approaches to sociolinguistic variation, the book provides a systematic overview of such topics as: 'English' as a social and as a linguistic concept The relationship between regional and social dialectology, and their application to the study of English English historical sociolinguistics, from Old English to late Modern English Sociolinguistics and change in English Outcomes of contact involving varieties of English English and language planning English, sociolinguistics and linguistic theory. The book contains data drawn from studies of English as it is used around the world. Throughout, there is an emphasis on facilitating a deeper understanding of linguistic variation in English and the social, political and cultural contexts in which speakers and writers of English operate.